Music videos as cultural artefacts of the eighties - Retha Van Niekerk (Communicare)
A overview of the development of movements in art and music during the twentieth century is given to place music videos in perspective as cutural phenomena reflecting certain artistic, philosophical and social tendencies of the present. Music videos, are seen against the back ground of the semiological view that a cultural artefact does not simply reflect society, it also acts as a "signifying practice with its own determinate product: meaning" (Hall 1980:30). A semiological approach Incorporating concepts from structuralism, psychoanalysis, feminism and post-structuralism is used to construct a theoretical model for the analysis of meanings in the visual images of music videos. In the theoretical model three levels of meaning, namely denotative, connotative and mythical, are distinguished with certain qualititative elements defined on each level The denotative level or the level of reality contains iconic signs, indexical signs and symbolical signs. Other qualitative elements include characters, setting, and descriptions of primary movements. The connotative level or the level of representation includes television codes (non-filmic and filmic), narrative codes and intertextual codes The level of myth or the level of ideology includes stylistic or textual devices such as metaphors, allegories, fetishism, voyeurism and parody. This article is that music videos function as mod- ern artefacts which have the potential to express complex cultural meanings to signal a new Weltanschauung (Lorch 1988:143)